Identity and Belonging: Emotional Assimilation in Two Immigrant Communities in Germany - Hansen Michael A.; Olsen Jonathan (Springer, 2025)
In this article, we analyze emotional assimilation (host country identification) within Germany’s two largest immigrant communities—ethnic Germans from the former Soviet Union and those German citizens with an ethnic Turkish migration background. Specifically, we investigate the strength of emotional assimilation among these two communities and the differences that might exist between them. To what degree have these two large immigrant communities cultivated a sense of host country identification or German national identity? What factors shape emotional assimilation in these two communities? We find that ethnic German citizens with a background from the former Soviet Union have a stronger German identity than do citizens with a Turkish background. Nevertheless, the difference between these two groups is substantively small, perhaps because the transformation of immigration rules, citizenship laws, integration policies, and social norms in Germany over the last two decades has led to a greater identification with Germany and its emerging multicultural society.